Diagnosis of lesion with statistical method of Anova1 & two ways for multi-MRI images with format. dicom - El Kourd, Kaouther; ., Atianaoual; Bouaicha, Abdenour; Benkraouda, Souleyman (International Journal of Engineering and Technology, 2017)
This paper deals with real time surface detection for image processing and analysis. We propose an appropriate analysis method with analysis of variance two ways to detect all surfaces of images in accuracy time. The results indicate that Anova_2 converged to the solution in accuracy time in comparison with Anova_1 for linear model.
Keywords: Anova; 1; Anova 2; Statistical; Regression.